2006
DOI: 10.1111/j.1444-2906.2006.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of zinc with connective tissue in the digestive tract of common carp

Abstract: Zinc (Zn) concentration in the digestive tract of common carp is always >10 times higher than most animal tissues. In a previous paper, it was reported that this high Zn came from a 43 kDa Zn-binding membrane protein. In this present study it was further found that in the digestive tract of common carp, Zn content was closely associated with the amounts of extracellular macromolecules. The higher the Zn content, the more there is of collagen and glycosaminoglycans. An indirect immunoperoxidase staining method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
4
12
0
Order By: Relevance
“…Significantly higher Zn concentrations in tissues of common carp than in other four fish species might be caused by its specific physiology. This is in line with the findings of Jeng and Sun (1981) and Liao et al (2006) that Zn concentrations in common carp digestive tract are always >10 times higher than in most of the animal tissues. Our results are in accordance with the findings of other authors, namely that the highest elemental concentrations are accumulated in metabolically active tissues such as liver and gills (Rashed, 2001;Dural et al, 2006;Erdogrul and Erbilir, 2007;Kenšova et al, 2010;Poleksić et al, 2010), while muscles commonly have lower elemental concentrations (Çalta and Canpolat, 2006;Ploetz et al, 2007;Agah et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Significantly higher Zn concentrations in tissues of common carp than in other four fish species might be caused by its specific physiology. This is in line with the findings of Jeng and Sun (1981) and Liao et al (2006) that Zn concentrations in common carp digestive tract are always >10 times higher than in most of the animal tissues. Our results are in accordance with the findings of other authors, namely that the highest elemental concentrations are accumulated in metabolically active tissues such as liver and gills (Rashed, 2001;Dural et al, 2006;Erdogrul and Erbilir, 2007;Kenšova et al, 2010;Poleksić et al, 2010), while muscles commonly have lower elemental concentrations (Çalta and Canpolat, 2006;Ploetz et al, 2007;Agah et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…This may improve protein synthesis and growth (Apines-Amar et al, 2004) and it also increases synthesis of IGF-1 and bone protein (Ma & Yamaguchi, 2001ab). Literature reports that dietary mineral supplementation increases enzyme activity (Apines-Amar et al, 2004;Liao et al, 2006;Cho et al, 2006), which could also be observed in this study. However, the activity of alkaline phosphatase in the plasma of fish fed zinc non-supplemented diets was similar to the fish fed diet supplemented with 12.0Yst:1.200Zn.…”
Section: Resultssupporting
confidence: 87%
“…This could be the result of pollution of the Danube and Sava Rivers (Crnković et al, 2008), of inversely correlated Zn concentrations with the trophic level (Papagiannis et al, 2004), as well as of carp physiology (Jeng and Sun, 1981;Liao et al, 2006). The significant differences in concentrations of As in liver and gills of burbot, as well as of Hg in liver and gills of piscivorous Table 2 The inter-group comparisons between pairs of species for concentration of elements in specified tissues performed by the non-parametric Mann-Whitney test (p o 0.05).…”
Section: Discussionmentioning
confidence: 98%